A three-dimensional analytical approach for large rectangular splitter silencers in the presence of mean flow. (24th November 2021) - Chen, Lingfeng; Wang, Xiaoyu; Du, Lin; Sun, Xiaofeng
Abstract: The dissipative splitter silencer is a common means for broadband noise attenuation in flow ducts such as ventilation and gas turbine systems where many higher order modes are cut-on. To predict the effect of a splitter silencer, analytical approaches have obvious advantages over the numerical methods on computation efficiency, but the development of analytical approaches are often based on many simplifications like the infinite length assumption. This paper presents a three-dimensional analytical method to solve the sound propagation in a duct with a finite length splitter silencer in the presence of mean flow. In the developed method, the convergence problem, which is often encountered by using the existing mode-based methods for high-frequency computations of soft-wall eigenmodes, is overcome by applying the equivalent surface source concept. With very low computational cost, the present method is validated to give consistent transmission loss predictions with the numerical results and experimental measurements available in the literature. Further, the performance of a splitter silencer is studied with different higher order incident modes, and reflection versus dissipation analysis is conducted by using the developed method. It is found that the sound attenuation is dependent on the sound energy spatial distributions of the incident sound modes, and the dissipation dominates the transmission loss behavior of the splitter silencer.